Workplace psychosocial resources and risk of cardiovascular disease among employees: a multi-cohort study of 135 669 participants - Xu, Tianwei; Rugulies, Reiner; Vahtera, Jussi; Pentti, Jaana; Mathisen, Jimmi; Lange, Theis; Clark, Alice J.; Magnusson Hanson, Linda L.; Westerlund, Hugo; Ervasti, Jenni; Virtanen, Marianna; Kivimäki, Mika; et al. (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVE ': 'In terms of prevention, it is important to determine effects on cardiovascular disease (CVD) when some workplace psychosocial resources are high while others are low. The aim of the study was to assess the prospective relationship between clustering of workplace psychosocial resources and risk of CVD among employees. ' ' METHODS ': 'We pooled data from three cohort studies of 135 669 employees (65% women, age 18–65 years and free of CVD) from Denmark, Finland and Sweden. Baseline horizontal resources (culture of collaboration and support from colleagues) and vertical resources (leadership quality and procedural justice) were measured using standard questionnaire items. Incident CVD, including coronary heart and cerebrovascular disease, was ascertained using linked electronic health records. We used latent class analysis to assess clustering (latent classes) of workplace psychosocial resources. Cox proportional hazard models were used to examine the association between these clusters and risk of CVD, adjusting for demographic and employment-related factors and pre-existing physical and mental disorders. ' ' RESULTS ': 'We identified five clusters of workplace psychosocial resources from low on both vertical and horizontal resources (13%) to generally high resources (28%). High horizontal resources were combined with either intermediate [hazard ratio (HR) 0.84, 95% confidence interval (CI) 0.74–0.95] or high (HR 0.88, 95% CI 0.78–1.00) vertical resources were associated with lower risks of CVD compared to those with generally low resources. The association was most prominent for cerebrovascular disease (eg, general high resources: HR 0.80, 95% CI 0.67–0.96). ' ' CONCLUSIONS ': 'Individuals with high levels of workplace psychosocial resources across horizontal and vertical dimensions have a lower risk of CVD, particularly cerebrovascular disease.
Keywords: cardiovascular disease; collaboration; leadership quality; multi-cohort study; procedural justice; psychosocial; psychosocial resource; social support